2017
DOI: 10.1128/aem.00140-17
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Drug-Resistant Salmonella enterica Isolates from Dairy Cattle and Humans in New York and Washington States Reveals Source and Geographic Associations

Abstract: Multidrug-resistant (MDR) Salmonella enterica can be spread from cattle to humans through direct contact with animals shedding Salmonella as well as through the food chain, making MDR Salmonella a serious threat to human health. The objective of this study was to use whole-genome sequencing to compare antimicrobial-resistant (AMR) Salmonella enterica serovars Typhimurium, Newport, and Dublin isolated from dairy cattle and humans in Washington State and New York State at the genotypic and phenotypic levels. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
107
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 66 publications
15
107
1
1
Order By: Relevance
“…Previously, WGS has been used to differentiate drug-resistant S. enterica isolates from different locations, which can exhibit notable differences in resistant-relevant genotypic and phenotypic characteristics (34). Other research has shown WGS can be valuable in predicting phenotypic resistance among both S. enterica (34, 35) and E. coli (36). In the current study, WGS analyses revealed that all our Subgroup B2 isolates carried bla TEM - 1 and tetA.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, WGS has been used to differentiate drug-resistant S. enterica isolates from different locations, which can exhibit notable differences in resistant-relevant genotypic and phenotypic characteristics (34). Other research has shown WGS can be valuable in predicting phenotypic resistance among both S. enterica (34, 35) and E. coli (36). In the current study, WGS analyses revealed that all our Subgroup B2 isolates carried bla TEM - 1 and tetA.…”
Section: Discussionmentioning
confidence: 99%
“…Partial genes only accounted for 6.4% of streptomycin discrepancies, suggesting this observation is not due to potential non-functional genes. While the mechanism of discordance between streptomycin resistance genes and susceptibility is unclear, this relationship has been observed in multiple surveys of Enterobacteriaceae (14, 16, 51, 54, 55). [also see S. 8]…”
Section: Resultsmentioning
confidence: 97%
“…Similar phylogeographical separation has also been observed in S. Dublin as well. Strains isolated from New York and Washington states cluster into distinct clades (9). We did not consider within country clustering due to the paucity of certain samples metadata (lack of specific region details).…”
Section: Discussionmentioning
confidence: 99%
“…Current genomics of S. Dublin has primarily focused upon the identification of antimicrobial resistance (AMR) homologues and mobile genetic elements such as prophages and plasmids (911). S. Dublin genome diversification appears to be driven by horizontal gene transfer and genome degradation resulting in pseudogenes (11).…”
Section: Introductionmentioning
confidence: 99%